Students' Voice: Wordwall as Game-Based Learning Media to Enhance Interest in Learning English - Maulida, Diva; Anjarsari, Dhania Puspita; Khusniyati, Nurul Ngaini; Indriani, Lilia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Wordwall is a Game-Based Learning media that can be used as a platform to enhance studentsâ€™ interest in learning English. This research aims to discover students' voices about Wordwall as a learning media and how Wordwall enhance students' interest in learning English. The researchers used qualitative research design which the instrument is a questionnaire provided offline survey using written paper. The data was obtained from 40 undergraduate students taken from general English courses at one of the prestigious state universities in Central Java, Indonesia. In the application of Game-Based Learning in this study, students must understand the use of Wordwall in the form of practice questions to improve their English skill development.Â  From the analysis of students' voices, this research successfully shows that 95% of students consider Wordwall as Game-Based Learning to be an interactive and fun learning media. From this agreement, there are three issues obtained from students' voices, such as Wordwall has various themes, easy to understand, and many animation features have the highest percentage in this study. However, 5% of students who are constrained in using Wordwall as an English learning media because it is difficult to access and understand the features. However, the results of this study cannot simplify the application of Wordwall in another general subject. Thus, further researchers who are interested in studying issues relevant to this study are advised to use in-depth interviews related to the implementation of Wordwall learning media with teachers and students. Implementation of Wordwall learning media to teachers and students, as well as research in schools that have internet networks.